P.103 When a neurosurgeon should care about pneumonia: the case for Pneumocystis jirovecii pneumonia prophylaxis in neurosurgical patients. (5th June 2019) - de Lotbiniere-Bassett, M; Dhillon, M; Boiteau, PJ; Couillard, P
Abstract : Background: Pneumocystis jirovecii pneumonia (PJP) is an opportunistic interstitial fungal pneumonia. The incidence of PJP in HIV-positive populations is decreasing, while it is increasing in HIV-negative immunocompromised populations, such as neurosurgical patients treated with high-dose corticosteroids. Morbidity and mortality can be severe owing to acute respiratory failure.Methods: Two cases are described and a literature review performed to determine the incidence of PJP in the neurosurgery population. A standardized care pathway is proposed to reduce preventable harm.Results: Long-term, high-dose corticosteroid regimens (≥4 mg dexamethasone daily for ≥4 weeks) with taper are associated with increased risk of PJP infection. Additional risk factors for infection in HIV-negative patients include CNS malignancy and concurrent radiation therapy. TMP-SMX is the first-line agent for PJP prophylaxis.Conclusions: Clinicians should maintain a high index of suspicion of PJP and adopt a standardized protocol for prophylaxis in neurosurgical patients treated with high-dose corticosteroids.